Regional Superior Products as The Key to Sustainable Food Security in Jember Regency, Indonesia - Hariono, Budi; Kurnianto, Mokhamad Fatoni; Wijaya, Rizza; Brilliantina, Aulia; Galushasti, Andarula; Bintoro, Mochamat (P3M Politeknik Negeri Jember, 2024)
Understanding the development planning priorities and commodity sub-sector in Jember Regency, it is necessary to acknowledge the prime sub-sector and the primary commodity sector in Jember Regency. Regional products should be able to prioritize the sub-sector and the preferred crop, prime and which is considered a sub-sector basis to optimize the food security in the region. The research was conducted from 2016 to 2021 by several analysis methods: Location Quotient, Analytical Hierarchy Process, and Exponential Comparative Method. The criteria used are based on seven normative criteria. The results showed that plantation and horticultural crops were the basis of sectors in the 2016-2020 survey, with values of 2,1036 and 1,3879. Based on the analytical hierarchy process and exponential comparative method analysis, it is seen that there are many leading commodities in the agriculture sector. These commodities are orange fruit, durian, banana, mushrooms, chili, coffee, and sugarcane.